2015
DOI: 10.1111/pirs.12112
|View full text |Cite
|
Sign up to set email alerts
|

Non‐linearities in regional growth: A non‐parametric approach

Abstract: This paper analyses the determinants of regional economic growth in the European Union adopting a non-parametric approach. Although the local-linear kernel estimator applied does not explicitly take into account the spatial dimension of the data, it is found to be consistent in our context. In addition, the geographically weighted regression turns out to be less efficient. We obtain evidence of a non-linear relationship between regional growth and its determinants in the form of parameter heterogeneity and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Clearly, integration in the European traffic networks is beneficial for trade and thus for economic development and growth. This variable has been found important, for example, in Sanso‐Navarro and Vera‐Cabello (). A dummy variable for capital regions (capital) is used. This variable has been found significant in Schneider and Wagner () and has posterior inclusion probability equal to one in Crespo Cuaresma and Feldkircher (), in line with the large literature on core‐periphery effects in new economic geography models (compare Fujita et al ., ).…”
Section: Datamentioning
confidence: 94%
“…Clearly, integration in the European traffic networks is beneficial for trade and thus for economic development and growth. This variable has been found important, for example, in Sanso‐Navarro and Vera‐Cabello (). A dummy variable for capital regions (capital) is used. This variable has been found significant in Schneider and Wagner () and has posterior inclusion probability equal to one in Crespo Cuaresma and Feldkircher (), in line with the large literature on core‐periphery effects in new economic geography models (compare Fujita et al ., ).…”
Section: Datamentioning
confidence: 94%
“…Therefore, kernel estimations will be able to control for spatial dependence when the regressors are close both in the variable and geographical spaces. Furthermore, Sanso‐Navarro and Vera‐Cabello () have shown that the local‐linear kernel estimator is more efficient than the alternative geographically weighted regression method (Brunsdon, Fotheringham, and Charlton, ). These arguments can be added to those in McMillen (, ) to advocate the use of nonparametric methods when dealing with spatial data and motivate their use to analyze the link between knowledge, innovation, and growth in European regions.…”
Section: Nonparametric Estimation Methodsmentioning
confidence: 99%
“…Similarly, Basile and Gress (), Basile () and Basile, Capello, and Caragliu () find nonlinear effects of the initial GDP per capita level and physical and human capital endowments. Sanso‐Navarro and Vera‐Cabello () conclude that nonlinearities mainly affect the initial productivity of labor, human capital, and the level of infrastructures. Adopting a distributional approach, Basile () only assigns a marginal role to nonlinearities in the accumulation of physical capital while Fiaschi and Lavezzi () find that the sectoral composition induces nonlinear growth patterns.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations